PERANAN PERKEMBANGAN INOVASI FINANSIAL SISTEM PEMBAYARAN DALAM MEMPENGARUHI PERMINTAAN UANG DI INDONESIA - Endah Siska Aristiyowati; Telisa Aulia Falianty (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2018)
This paper examines the dynamic interaction between financial innovation development in the payment system to money demand function especially for currency and narrow money, from 2007-2017 using Indonesia monthly data. This research based on Baumol (1952) and Tobin (1956) and Lippi and Secchi (2009) theory which stated that improvement of technology in the payment system will lead to a decrease in transaction demand for money. From estimation result using Vector Error Correction Model (VECM) method, study reveals that tremendous development in the payment system on the last eleven years i.e Real Time Gross Settlement, Clearing, Automatic Teller Machine (ATM)atauDebit Card, Credit Card and electronic money using several proxies, such as using transaction value (with and without clearing), total transaction value, transaction volume, ratio of financial innovation in the payment system to Gross Domestic Product (GDP), broad money (M2) to narrow money (M1) ratio, ratio of financial innovation in the payment system to narrow money (M1) will decrease currency and narrow money (M1). Analysis of the financial innovation in the payment system role in affecting money demand (currency and narrow money) is very important so that money demand function is not misspesificied and in determining monetary policy has considered the development of payment system technology.